Islamofobia Dan Implikasinya Terhadap Keamanan Nasional - Sarjito, Aris (Universitas Nasional, 2023)
AbstractIslamophobia is a phenomenon that refers to negative attitudes, silence, and anxiety toward Muslims and their way of life. This research investigates how Islamophobia impacts national security and the manifestations of this phenomenon in local and international communities. Islamophobia, fuelled by fear, ignorance, and media propaganda, leads to the ostracism and alienation of Muslims; Hence being isolated from an integral part of society which cannot contribute to the welfare of the nation.The implications of Islamophobia for national security go beyond a direct threat to public safety. This has far-reaching consequences for various aspects of society, including economic, educational, and immigration policies. Islamophobia threatens to undermine fundamental freedoms, such as freedom of religion and speech, and the right to a fair trial. It also threatens to damage international relations, particularly with Muslim-majority countries, and damage America's reputation on the world stage.Islamophobia has significant implications for national security, and the consequences are most effectively tackled by promoting education, dialogue, and mutual understanding. Government officials, law enforcement agencies, and the media must acknowledge the impact of Islamophobic rhetoric and policies and take steps to build bridges and promote tolerance and diversity. Embracing inclusion and multiculturalism can help promote a shared sense of national identity and promote greater harmony and cohesion in society.Keywords: islam, islamophobia, muslims, national security, radicalization